Quality of the living environment in the neighborhood of Murgle - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
The main characteristic that distinguishes the Murgle housing estate from other residential areas in Ljubljana is its specific and unique urban design inspired by Scandinavian urbanism. The main goal of the paper is to present an evaluation of residents' satisfaction with the quality of the living environment, 50 years after its construction commenced. We also analyzed gradual spatial, urbanistic and social transformations of the neighborhood over time. On the basis of the survey carried on among the residents we established that the neighborhood, despite many unregulated interventions not in accordance with its urban design, maintained a high quality of living environment.
Keywords: bivalno okolje; kvaliteta; Ljubljana; mesta; urbana geografija; urbanism; urbanizem